(untitled) (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2022)
A review of the radioecological situation in the Ural region after radiation accidents at the Mayak Production Association is presented. The results of the work of the staff of the Department of Continental Radioecology for assessing the pollution of freshwater ecosystems of the Ural region and Western Siberia are shown. The prognostic calculations of the concentration of radionuclides in the water and bottom sediments of lakes for 100 years, starting in 1957, have been performed.